Structure-Based Regulatory Role for the 5′UTR of RCNMV RNA2 - Jennifer S. H. Im; Jasmine R. Sheppard; K. Andrew White (Viruses, 2023)
Red clover necrotic mosaic virus (RCNMV) is a segmented positive-strand RNA virus consisting of RNA1 and RNA2. Previous studies demonstrated that efficient translation of RCNMV RNA2 requires de novo synthesis of RNA2 during infections, suggesting that RNA2 replication is required for its translation. We explored a potential mechanism underlying the regulation of replication-associated translation of RNA2 by examining RNA elements in its 5′ untranslated region (5′UTR). Structural analysis of the 5′UTR suggested that it can form two mutually exclusive configurations: a more thermodynamically stable conformation, termed the 5′-basal stem structure (5′BS), in which 5′-terminal sequences are base paired, and an alternative conformation, where the 5′-end segment is single stranded. Functional mutational analysis of the 5′UTR structure indicated that (i) 43S ribosomal subunits enter at the very 5′-end of RNA2; (ii) the alternative conformation, containing unpaired 5′-terminal nucleotides, mediates efficient translation; (iii) the 5′BS conformation, with a paired 5′-end segment, supresses translation; and (iv) the 5′BS conformation confers stability to RNA2 from 5′-to-3′ exoribonuclease Xrn1. Based on our results, we suggest that during infections, newly synthesized RNA2s transiently adopt the alternative conformation to allow for efficient translation, then refold into the 5′BS conformation, which supresses translation and promotes efficient RNA2 replication. The potential advantages of this proposed 5′UTR-based regulatory mechanism for coordinating RNA2 translation and replication are discussed.